ChemInform Abstract: Synthesis and Crystal Structure of δ‐TaON, a Metastable Polymorph of Tantalum Oxide Nitride. Issue 1 (January 2015) - Luedtke, Tobias; Schmidt, Alexander; Goebel, Caren; Fischer, Anna; Becker, Nils; Reimann, Christoph; Bredow, Thomas; Dronskowski, Richard; Lerch, Martin
Abstract δ‐TaON is prepared by ammonolysis of amorphous Ta2O5 precursor derived via a modified Pechini route (NH3 stream, 760 °C, 1 h; 43% yield).